Margarite - rock-forming mineral from Snezhnoe ruby deposit, Central Pamir - A. K. Litvinenko; Z. Z. Nasreddinov; E. S. Sorokina (Известия высших учебных заведений: Геология и разведка)
Margarite of Snezhnoe ruby deposit has been identified and studied as rock-forming mineral, being in paragenesis with ruby on Snezhnoe ruby deposit . It forms two morphological types: large and small scales. Its specific feature is a high content of 2О (1,43-4,37 mass %) and &2О3 (до 1,27 mass %). This finding allows carrying out of more close genetic linkages to those deposits, where margarite was known, such as Mogok (Myanmar), Taplejung District (Nepal), Hunza Valley (Pakistan), Jegdalek (Afghanistan), Kootchinskoye (Urals, Russia) etc.